2019
DOI: 10.7759/cureus.5015
|View full text |Cite
|
Sign up to set email alerts
|

A Fatal Case of Vancomycin Associated Drug Reaction with Eosinophilia and Systemic Symptoms Syndrome in a Septuagenarian

Abstract: Drug reaction with eosinophilia and systemic symptoms (DRESS) is a rare but potentially life-threatening multi-system disorder with a mortality rate of up to 10%, due to severe hypersensitivity drug reaction involving the skin and multiple internal organ systems. We emphasize the increasing prevalence of DRESS syndrome secondary to vancomycin use. A 79-year-old woman presented to the hospital with complaints of right upper quadrant pain, intense pruritis, and jaundice of one-week duration. She was on vancomyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…One case of vancomycin-induced ATN as a complication of DRESS is reported by Kim et al [ 53 ]. Vancomycin trough levels > 15 mg/L are an independent predictor of nephrotoxicity, but any relationship with DRESS has not been examined [ 54 ]. Based on our review, just in 3 cases out of 13 patients who trough level of vancomycin was reported for them, the level was higher than recommended range (23.08%).…”
Section: Discussionmentioning
confidence: 99%
“…One case of vancomycin-induced ATN as a complication of DRESS is reported by Kim et al [ 53 ]. Vancomycin trough levels > 15 mg/L are an independent predictor of nephrotoxicity, but any relationship with DRESS has not been examined [ 54 ]. Based on our review, just in 3 cases out of 13 patients who trough level of vancomycin was reported for them, the level was higher than recommended range (23.08%).…”
Section: Discussionmentioning
confidence: 99%
“…Vancomycin-induced DRESS tends to present with greater incidence of renal impairment compared with other drugs 2. Hepatic compromise from vancomycin-induced DRESS can be variable, with some patients presenting with significant transaminitis 3–5. Other patients may present with only a mild elevation in liver function tests; these patients tend to be younger and healthier, like the one presented in this report 6 7.…”
Section: Descriptionmentioning
confidence: 60%
“…Other patients may present with only a mild elevation in liver function tests; these patients tend to be younger and healthier, like the one presented in this report 6 7. Previously published cases of vancomycin-induced DRESS report onset of symptoms after at least 3 weeks of antibiotic therapy 3–7. This suggests that patients who require greater duration of vancomycin therapy, such as those with endocarditis or osteomyelitis, are at greater risk of developing DRESS.…”
Section: Descriptionmentioning
confidence: 62%
“…Ifosfamide is a synthetic analog of cyclophosphamide and is used for treating various solid cancers (1). On the other hand, it is an antineoplastic and cytotoxic medicine used to treat and manage diverse cancers, including sarcoma, lymphoma, lung cancer (2), soft tissue, and bone sarcomas (3). It is considered a bifunctional alkylating agent and metabolized by the P450 cytochrome (CYP450) system to active components.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered a bifunctional alkylating agent and metabolized by the P450 cytochrome (CYP450) system to active components. These active metabolites, including acrolein and ifosfamide mustard (3), inhibit DNA synthesis (2). There are two mechanisms for the action of these metabolites.…”
Section: Introductionmentioning
confidence: 99%